Peningkatan Kepemimpinan Transformasional dengan Organizational Citizenship Behavior (OCB) - Andi Hendrawan; Titi Laras; Hari Sucahyowati; Kristian Cahyandi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
The role of leadership is very strategic and important for the achievement of the mission, vision and goals of an organization, is one of the motives that encourage humans to always investigate the intricacies associated with leadership. Transformational leadership basically encourages subordinates to do better Behavior demanded by today's organizations is not only in-role behavior but also extra-role behavior. Extra-role behavior is also called the Organizational Citizenship Behavior.OCB is a term used to identify the employee behaviors that can be called a